Stat3 promotes IL-10 expression in lupus T cells through trans-activation and chromatin remodeling - Hedrich, Christian M. (National Academy of Sciences, 2014)
The immune-regulatory cytokine IL-10 plays a central role during innate and adaptive immune responses. IL-10 is elevated in the serum and tissues of patients with systemic lupus erythematosus (SLE), an autoimmune disorder characterized by autoantibody production, immune-complex formation, and altered cytokine expression. Because of its B cell-promoting effects, IL-10 may contribute to autoantibody production and tissue damage in SLE. We aimed to determine molecular events governing T cell-derived IL-10 expression in health and disease. We link reduced DNA methylation of the IL10 gene with increased recruitment of Stat family transcription factors. Stat3 and Stat5 recruitment to the IL10 promoter and an intronic enhancer regulate gene expression. Both Stat3 and Stat5 mediate trans-activation and epigenetic remodeling of IL10 through their interaction with the histone acetyltransferase p300. In T cells from SLE patients, activation of Stat3 is increased, resulting in enhanced recruitment to regulatory regions and competitive replacement of Stat5, subsequently promoting IL-10 expression. A complete understanding of the molecular events governing cytokine expression will provide new treatment options in autoimmune disorders, including SLE. The observation that altered activation of Stat3 influences IL-10 expression in T cells from SLE patients offers molecular targets in the search for novel target-directed treatment options.